Yield and composition of grain sorghum stover - R. L. Vanderlip; L.R. Schneider; K.K. Bolsen (Kansas Agricultural Experiment Station Research Reports, 1974)
Last year in Kansas approximately 3.8 million acres produced 243 million bushels of grain sorghum plus a large amount of forage left in the field as a potential source of feed for livestock. The objective of this report is to indicate the quantity of forage available after normal and early (high-moisture) harvest of sorghum grain.
Keywords: Cattlemen& #x27; s Day; 1974; Report of progress (Kansas State University. Agricultural Experiment Station); 210; Beef; Grain sorghum; Forage; Yield